(untitled) (Global Journal of Management and Business Research, 2023)
The author’s article is devoted to procedural justice in civil proceedings and factors affecting it. The author conducts research in her home country, i.e., the Republic of Latvia, on the practical consequences of the norms governing civil proceedings in connection with the application of case law, which the author associates with a factor affecting procedural justice. It should be explained here that the Republic of Latvia belongs to the continental European law group, therefore, the term case law means the highest court instances, i.e., Judgments of the Senate of the Supreme Court of the Republic of Latvia, which contain explanations about the correct application of the procedural and/or material norm or the interpretation of this norm. The influence of case law on the realization of substantive and procedural rights of individuals in the Republic of Latvia has three negative factors, against which there are still no protection mechanisms, i.e.: firstly, the case law is changing and the Senate of the Supreme Court can abandon its earlier explanations or interpretations regarding the application of the norm, but the new explanations can be diametrically opposed to the so-called " old". It may refer to substantive or procedural law.